Association Analysis of PRSS1-PRSS2 and CLDN2-MORC4 Variants in Nonalcoholic Chronic Pancreatitis Using Tropical Calcific Pancreatitis as Model. Issue 8 (September 2016) - Paliwal, Sumit; Bhaskar, Seema; Reddy, D Nageshwar; Rao, G Venkat; Thomas, Varghese; Singh, Shivaram Prasad; Chandak, Giriraj Ratan
Abstract : Objective: Association of PRSS1-PRSS2 (rs10273639) and CLDN2-MORC4 (rs12688220 and rs7057398) variants with alcohol-related chronic pancreatitis (CP) is established but with nonalcoholic CP is unclear. We addressed this inconsistency using tropical calcific pancreatitis (TCP) as model. Methods: We sequenced 5′-UTR of PRSS1 and genotyped CLDN2-MORC4 variants in 555 patients with TCP and 801 controls and performed association analysis. Gene-gene interaction between PRSS1 and CLDN2-MORC4 variants and with p.Asn34Ser SPINK1 and p.Leu26Val CTSB was also evaluated. Results: We observed significant association of rs10273639/rs4726576 in PRSS1-PRSS2 (odds ratio [OR] = 0.72; P = 3.50 × 10 −5 ) and CLDN2-MORC4 variants, rs12688220 (OR = 1.54; P = 1.22 × 10 −10 ) and rs7057398 (OR = 1.50; P = 1.22 × 10 −10 ) with TCP. Patients carrying p.Asn34Ser SPINK1 were significantly younger than those with rs4726576 risk genotype (30.0 vs 38.0 years; P = 0.015) and those carrying both were even younger (22.0 years; P = 0.001). Presence of risk allele at rs12688220 in patients carrying p.Asn34Ser SPINK1 delayed the age of onset (32.0 vs 24.0 years; P = 0.013). Conclusions: Our study establishes strong association of PRSS1-PRSS2 and CLDN2-MORC4 variants with TCP and thus with nonalcoholic CP. These variants independently interact with p.Asn34Ser SPINK1 and influence the age of onset in TCP. However, latter results need to be replicated in other cohorts.